A loading pattern optimization method based on discrete differential evolution. (March 2020) - Ding, Hui; Sun, Guangyao; Hao, Lijuan; Wu, Bin; Wu, Yican
Highlights: Optimization of a core loading problem (LP) for a commercial reactor is considered. A discrete differential evolution algorithm was developed for LP optimization. The algorithm and a SuperMC code were applied to WBN1's power flattening. The optimized LP outperformed WBN1 designer LP for PPF. Abstract: Core loading pattern (LP) optimization is a combinatorial optimization problem with significant impact on the economic and safety performance of a reactor. However, finding an optimal solution for core loading patterns is a very complex problem due to the large number of combinations of fuel assemblies. For this paper, a loading pattern optimization method based on discrete differential evolution was developed. To evaluate the method, a program coupled with SuperMC was developed and validated using a PWR test case. The program was then applied to minimize the radial power peak factor of the Watts Bar Nuclear 1 reactor under the constraint of the criticality state of the reactor. The results showed the discrete differential evolution to be reliable and effective in LP optimization.